Futures of autonomous flight: Using a collaborative storytelling game to assess anticipatory assumptions. (April 2021) - Belton, Olivia; Dillon, Sarah
Highlights: Collaborative storytelling games enable assessment of anticipatory assumptions. Flexible method for understanding technological futures with diverse stakeholders. Failure, trustworthiness and climate anxieties key to autonomous flight perception. Concerns revealed that may appear tangential to possible or plausible technical futures. Collaborative storytelling is an adaptable method to generate imagined technological futures. Abstract: The passenger aviation industry has embraced electronic automation. Fully autonomous passenger flight is a near-future technical possibility, but questions remain regarding how potential air travellers might receive such a technological leap. This paper contributes to and expands the existing literature on public perceptions of autonomous flight, presenting the results of an exploratory study of non-expert anticipatory assumptions (AA). A new collaborative storytelling futures method was designed, combining the benefits of the functions of stories as anticipatory systems with the stronger participatory advantages of games. The study conducted three focus groups with self-selected public participants to generate participatory stories set in futures where autonomous aircraft were prevalent. The qualitative analysis of the stories demonstrates that non-experts situate their beliefs and attitudes towards new technologies within frameworks indebted to their present cultural and political context. Public perception of autonomous flight is determined by AA including technological failure, the trustworthiness of business and governments, and the climate crisis. Work remains to be done if relevant stakeholders wish to communicate potential positive effects of autonomous flight technology. This research demonstrates the value of collaborative storytelling as a highly adaptable method to generate futures involving a wide variety of technologies.